2018
DOI: 10.6004/jnccn.2017.7047
|View full text |Cite
|
Sign up to set email alerts
|

Community Oncologists' Decision-Making for Treatment of Older Patients With Cancer

Abstract: Background This study’s objectives were to describe community oncologists’ beliefs about and confidence with geriatric care and to determine whether geriatric-relevant information influences cancer treatment decisions. Methods Community oncologists were recruited to participate in two multi-site geriatric oncology trials. Participants shared their beliefs about and confidence with caring for older adults. They were also asked to make a first-line chemotherapy recommendation (combination vs. single-agent vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 50 publications
(58 reference statements)
0
66
0
Order By: Relevance
“…One fundamental strategy is the use of a GA in the oncology clinic, which is recommended for all older adults with cancer by the American Society of Clinical Oncology (ASCO), the National Comprehensive Cancer Network, and the International Society of Geriatric Oncology [43,[48][49][50]. Despite these recommendations, the implementation of the GA in daily oncology practice has been slow; this is, in part, due to the perception that it is time consuming [51]. However, the ASCO guideline notes that the GA is feasible to complete in both clinical trials and in the oncology clinic, takes about 20-30 minutes to complete, and can be obtained via a paper or electronic record [43].…”
Section: Measurement Of Cachexia and Sarcopenia In Older Adultsmentioning
confidence: 99%
“…One fundamental strategy is the use of a GA in the oncology clinic, which is recommended for all older adults with cancer by the American Society of Clinical Oncology (ASCO), the National Comprehensive Cancer Network, and the International Society of Geriatric Oncology [43,[48][49][50]. Despite these recommendations, the implementation of the GA in daily oncology practice has been slow; this is, in part, due to the perception that it is time consuming [51]. However, the ASCO guideline notes that the GA is feasible to complete in both clinical trials and in the oncology clinic, takes about 20-30 minutes to complete, and can be obtained via a paper or electronic record [43].…”
Section: Measurement Of Cachexia and Sarcopenia In Older Adultsmentioning
confidence: 99%
“…Both aforementioned studies demonstrated that a geriatric assessment could be helpful in guiding treatments. When relevant geriatric information is available to oncologists, it has been shown that treatment decision-making does change [ 38 , 39 ]. While geriatric assessment-guided AML studies are lacking, available data from varied settings do suggest that if geriatric assessment information is available to oncologists, decisions to treat more or less aggressively are altered; some patients receive more aggressive treatment based on evidence of fitness and others receive less aggressive therapies once existing vulnerabilities or frailty are demonstrated.…”
Section: Benefits Of Geriatric Assessmentmentioning
confidence: 99%
“…Dr. Mohile and Dr. Dale are currently examining how GAs can be further integrated into oncology clinics to improve patient care. “Community oncologists want to do these assessments, but we found that less than 25% were using them,” Dr. Mohile says. “We have to change the practice structure so it's amenable to doing GAs.”…”
Section: Integrating Geriatric Assessmentsmentioning
confidence: 99%